Enkripsi dan Dekripsi Pesan Menggunakan Polinomial Galois Field dengan Algoritma Hill Cipher - Vega, Amelia; Sujarwo, Imam; Khudzaifah, Muhammad (Jurnal Riset Mahasiswa Matematika, 2022)
An information is extremely easy to obtain when technology is evolving so fast and it is important to secure the information to avoid irresponsible parties who want to abuse it. Messages that are not safe will harm the owner of the message, therefore a lot of research is related to message security. This study aims to deepen the message security in encoded form using Galois Field polynomials with one of the symmetric encryption algorithms, namely the Hill Cipher algorithm. Encryption is the process of converting a message into a secret code while decryption is the reverse process. The encryption and decryption process in this discussion is carried out by changing the message character into Galois Field polynomial form, then operating calculations based on the Hill Cipher algorithm, and then changing the results of the calculation operations into character form again. Based on the modifications have been made, the encryption and decryption formulas will be multiplied by modulo in polynomials form. In this study, the encryption and decryption keys are in matrix form with elements in it are members of the Galois Field polynomial and the result is a random message of 256 characters in binary bit-8. From this research, we gain insight into the encoding that can be done using polynomials which can be used later in other forms of encoding.